Metamaterial-based real-time communication with high information density by multipath twisting of acoustic wave - Kai Wu; Jing-Jing Liu; Yu-jiang Ding; Wei Wang; Bin Liang; Jian-Chun Cheng (Nature Communications, 2022)
Here, the authors demonstrate multipath twisting of acoustic waves with a thin metamaterial layer enabling high-speed transfer of information with no time-consuming post-processing or sensor scanning, showing important application potential in underwater communication.